TAX REVENUE - THE DETERMINANT FACTORS- THE CASE OF ALBANIA - Entela Velaj; Llambi Prendi (European Scientific Journal, ESJ, 2014)
The purpose of this paper is to analyze the factors that will increase or will reduce revenues from taxes collected by the government. The variables that we have took in consideration are GDP, inflation, income tax, unemployment and imports. We have used the statistical analysis to see if there is a connection between the variables that we have chosen as explanatory ones. Through the use of the logarithmic function we will see how flexible is the GDP of our country related to income from taxes and government spending. The data that we have analyzed are obtained from the Ministry of Finance, INSTAT, World Bank, etc..